Cleft and Craniofacial Team Orthodontic Care in the United States: A Survey of the ACPA. (August 2019) - Khavanin, Nima; Jenny, Hillary; Jodeh, Diana S.; Scott, Michelle A.; Rottgers, S. Alex; Steinberg, Jordan P.
Objective: To better understand the capacity for orthodontic care, service features, and finances among members of the American Cleft Palate-Craniofacial Association (ACPA). Design: Cross-sectional survey. Setting: ACPA-approved multidisciplinary cleft teams. Participants: Cleft team coordinators. Interventions: Coordinators were asked to complete the survey working together with their orthodontists. Main Outcome Measure: Model for orthodontic care. Results: Coordinators from 82 out of 167 teams certified by ACPA completed the survey (response rate = 49.1%). Most orthodontists were private practice volunteers (48%) followed by university/hospital employed (22.8%). Care was often delivered in community private practice facilities (44.2%) or combination of university and private practice facilities (39.0%). Half of teams reported offering presurgical infant orthopedics (PSIO), with nasoalveolar molding being the most common. Cleft/craniofacial patients typically comprise 25% or less of the orthodontists' practices. The presence of a university/hospital-based orthodontist was associated with higher rates of offering PSIO ( P < .001) and an increased percentage dedication of their practice to cleft/craniofacial care ( P < .001). Conclusion: Orthodontic models across ACPA-certified teams are highly varied. The employment of full-time craniofacial orthodontists is less common but is highly correlated with a practice with a high percentage of cleft care and the offering of advanced services such as PSIO. Future work should focus on how to effectively promote such roles for orthodontists to ensure high-level care for cleft/craniofacial patients requiring treatment from infancy through skeletal maturity.